Pengaruh Literasi Keuangan dan Faktor Demografi terhadap Minat Masyarakat Berinvestasi Di Pasar Modal (Studi Kasus Pada Masyarakat usia 21-35 Tahun di DKI Jakarta) - Anggarini, Vellaniar Yunias; Riyadi, Selamet (Jurnal Ilmu Manajemen, 2022)
This study aims to analyze and obtain empirical evidence of the influence of financial literacy and demographic factors on public interest in investing in the capital market. This research is a quantitative research with data collection methods using questionnaires distributed to the public in DKI Jakarta with the condition that people who already have income which are 4,836,980 correspondents. A minimum sample of 100 respondents is obtained by calculating the sample using the Slovin technique and data processing is assisted by using SPSS statistical software, the feasibility test of the data in this study uses validity and reliability tests, while for the analytical method using descriptive analysis, classical assumption test, multiple linear regression analysis and hypothesis testing. The results of this study are financial literacy has no significant effect on people's interest in investing in the capital market, while demographic factors have a significant effect on public interest in investing in the capital market but after a feasibility test on the two independent variables the results are both variables have a significant effect on people's interest in investing in the capital market. capital market